„Die Macht des Heiligen“ als eine Alternative zur Entzauberung?: zu Hans Joas’ Religionstheorie - Schwinn, Thomas (Berliner Journal für Soziologie, 2019)
The past decades have witnessed a controversial debate around the concept of “secularization”. Adding to this line of thought, Hans Joas has recently published a book on Die Macht des Heiligen (The power of the sacred), wherein he presents an alternative to the Weberian notion of “disenchantment”. The article critically reflects on the theoretical argument of the book. Therein, Joas argues that Weber’s theory of religion, from which he derives his untenable thesis of disenchantment, was fundamentally misconstructed. Consequently, Weber misunderstood the relation between transcendency and immanence, leading him to falsely assume a general historical process of secularization (Verweltlichung). In contrast, Joas argues for an anthropological understanding of “self-transcendency”, which hadn’t lost its potential even in the course of modernity. Besides criticizing interpretation of Weber, the article asks to what extent experiences of “self-transcendency” may indeed shape social order and life conduct under modern conditions. The concluding part reflects on the influence of Joas’s personal faith on his scientific thinking.